2009
DOI: 10.1007/s00464-009-0373-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of skin adhesives versus sutures in closure of laparoscopic port-site wounds

Abstract: Based on this review, there is insufficient evidence that port-site wound closure technique by tissue adhesives is superior to traditional suture closure technique in terms of wound infection, wound dehiscence, and patient satisfaction. However, tissue adhesives are quicker in port-site wound closure. A multicentre randomized controlled trial is required in order to obtain stronger evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Sutures compared to 2OCATI showed no difference in length of inpatient stay, mean total cost, or antibiotics treatment [4]. Laparoscopic port site incisions were closed faster by surgical adhesive than sutures in a metaanalysis of seven trials [5]. Among general surgery laparoscopic procedures, a randomized controlled trial of n-butyl cyanoacrylate tissue adhesive versus sutures showed significantly shorter incision closure times and no differences in wound complications or cosmesis at either 4 to 6 weeks or at 3 months [6].…”
Section: Discussionmentioning
confidence: 98%
“…Sutures compared to 2OCATI showed no difference in length of inpatient stay, mean total cost, or antibiotics treatment [4]. Laparoscopic port site incisions were closed faster by surgical adhesive than sutures in a metaanalysis of seven trials [5]. Among general surgery laparoscopic procedures, a randomized controlled trial of n-butyl cyanoacrylate tissue adhesive versus sutures showed significantly shorter incision closure times and no differences in wound complications or cosmesis at either 4 to 6 weeks or at 3 months [6].…”
Section: Discussionmentioning
confidence: 98%
“…1,2 A study with a large retrospective questionnaire on 262,000 arthrograms reported a complication rate of 3.6% and 0.03% of these complications were severe. 1 Another study reported sterile chemical synovitis as the most common adverse reaction following arthrography. Figure 1 Plain radiography demonstrating an intracapsular air ring following air arthrography…”
Section: Discussionmentioning
confidence: 99%
“…A metananlysis based on four clinical trials encomassing 404 patients showed that there is insufficient evidence that port-site wound closure technique by tissue adhesives is superior to traditional suture closure technique in terms of wound infection, wound dehiscence, and patient satisfaction. 20 Finally the Cochrane review in which eight RCTs (630 patients) on comparison of tissue adhesives and sutures were included no statistically significant difference was found for dehiscence, infection or cosmetic appearance. However a statistically significant difference was found for surgeons' assessment of cosmetic appearance with mean difference 13 (95% CI 5 to 21), the higher mean rating for the tissue adhesive group.…”
Section: Discussionmentioning
confidence: 99%